2017
DOI: 10.1142/s021773231730035x
|View full text |Cite
|
Sign up to set email alerts
|

Recent searches for continuous gravitational waves

Abstract: Gravitational wave astronomy opened dramatically in September 2015 with the LIGO discovery of a distant and massive binary black hole coalescence. The more recent discovery of a binary neutron star merger, followed by a gamma ray burst and a kilonova, reinforces the excitement of this new era, in which we may soon see other sources of gravitational waves, including continuous, nearly monochromatic signals. Potential continuous wave (CW) sources include rapidly spinning galactic neutron stars and more exotic po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
141
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(142 citation statements)
references
References 432 publications
(742 reference statements)
1
141
0
Order By: Relevance
“…The canonical sources for CWs (see [3] for a review) are non-axisymmetric rotating neutron stars, emitting long-lasting and nearly monochromatic waves. When observed from Earth, these waves will be frequency modulated due to the Doppler effect produced by the daily rotation and orbital motion of the Earth around the Sun.…”
Section: Introductionmentioning
confidence: 99%
“…The canonical sources for CWs (see [3] for a review) are non-axisymmetric rotating neutron stars, emitting long-lasting and nearly monochromatic waves. When observed from Earth, these waves will be frequency modulated due to the Doppler effect produced by the daily rotation and orbital motion of the Earth around the Sun.…”
Section: Introductionmentioning
confidence: 99%
“…Another more exotic source of CWs are ultra-light bosons clouds orbiting BHs [4]. A comprehensive review of potential CW sources can be found in [5].…”
Section: Introductionmentioning
confidence: 99%
“…where I zz is the star moment of inertia around the rotation axis (z-axis) while = Ixx−Iyy Izz is the ellipticity. To date several CW investigations took place and, although no signal has been detected so far, stringent upper limits on the GW amplitude have been placed [5]. Each search uses a different method and is dependent on the parameter space investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Rotating NSs are potential sources of high-frequency CWs [24,25]; a NS with a non-zero quadrupolar moment is expected to emit GWs at a frequency f GW = 2ν, where ν is the rotational frequency of the NS [26]. For known pulsars with measured time derivatives, a rough upper limit on the strength of emitted GWs can be obtained by assuming its spin-down is solely due to energy emitted in GWs.…”
Section: Continuous Gws or Compact Binary Coalescencesmentioning
confidence: 99%